Z-ligustilide attenuates lipopolysaccharide-induced proinflammatory response via inhibiting NF-κB pathway in primary rat microglia - Wang Jing; Du Jun-rong; Wang Yu; Kuang Xi; Wang Cheng-yuan (Acta Pharmacologica Sinica; Vol 31, No 7 (July 2010): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anti-inflammatory effect of Z-ligustilide (LIG) on lipopolysaccharide (LPS)-activated primary rat microglia. Methods: Microglia were pretreated with LIG 1 h prior to stimulation with LPS (1 μg/mL). After 24 h, cell viability was tested with MTT, nitric oxide (NO) production was assayed with Griess reagent, and the content of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and monocyte chemoattractant protein (MCP-1) was measured with ELISA. Protein expression of the nuclear factor-κB (NF-κB) p65 subunit, cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) was detected with immunocytochemistry 1 h or 24 h after LPS treatment. Results: LIG showed a concentration-dependent anti-inflammatory effect in LPS-activated microglia, without causing cytotoxicity. Pretreatment with LIG at 2.5, 5, 10, and 20 μmol/L decreased LPS-induced NO production to 75.9%, 54.4%, 43.1%, and 47.6% (P